SOFTWARE TEST AUTOMATION FOR AUTOMATED SYSTEMS OF SLIDING FORMWORK - Dmitry A. Korotky (Вестник Донского государственного технического университета, 2018)
The universal test system model, which permits to structurally describe test automation tasks aimed at the efficient use of the existing test toolkits and the creation of new ones, is considered.